Implementasi E-Government Pada Aplikasi DILANDACITA Dinas Kependudukan dan Pencatatan Sipil Kota Cimahi - Putri Dhiya Deyani; Indah Sevtyaning Choirunnisa; Salsabilla Putri Nurimani; Ivan Darmawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The implementation of e-government in Dilandacita application is a progressive step in theÂ  transformation of public services at the Population and Civil Registration Office of Cimahi City. Dilandacita is designed to make it easier for people to apply for population administration services in real time with only an internet connection and browser. Using descriptive qualitative research method, this research focuses on analyzing the implementation of e-government, especially the concept, objectives, and performance of e-government (Indrajit, 2002). The result is based on the Community Satisfaction Index, Dilandacita application received a score of 80,575 from a total of 13,542 respondents (users). The implementation of Dilandacita can be said to be good and improve administrative efficiency, optimize the transaction process, and provide better accessibility for the community. In addition, the government can increase transparency, public participation, and form a modern, efficient, and sustainable public service ecosystem.